Studies on the Manner of Collateral Regeneration From Nerve Stem to Motor Endplate - Qi, Zhidan; Li, Dongdong; Li, Li; Meng, Dexuan; Deng, Jin; Jin, Bo; Gu, Xinyi; Wang, Shen; Huang, Chen; Yin, Xiaofeng (Frontiers in Physiology, 2022)
Despite recent evidence suggesting that nerve transfer techniques help improve clinical outcomes,the underlying manner by which collateral regenerated nerve enters skeletal muscles to restore an organized pattern of NMJ is unclear.To construct the animal models of collateral regeneration, the proximal peroneal nerve was fixed to the distal tibial nerve stump. Three months after surgery, the spatial distribution of MEPs and corresponding in-muscle nerve branches in long flexor digitorum (LFD) muscles was observed with tissue optical clearing combined with light-sheet microscopy in transgenic fluorescent mice. The results showed that the number of fibers in proximal donor peroneal nerve was 415±11, while regenerated nerve fibers in distal tibial stump was 781±43,which means a collateral regeneration ratio of 1.88.The spatial distribution of MEPs were restored to an organized pattern of lamella and the corresponding in-muscle nerve branches reverted to a normal manner as such after collateral regeneration. Beyond this, the number of MEPs dominated by single distal nerve fiber were 25.58±0.50 and 26.42±0.94, respectively (n = 6, P>0.05, collateral regeneration group vs normal group).However, the numbers of distal regenered nerve fibers were less than normal control groups(781±43 vs 914±55, n = 6, p < 0.05) and the number and perforations of MEPs were lower than normal control groups as such.In summary,it is the first time to show the manner of collateral regeneration of peripheral nerve that the smaller proximal donor nerve can sprout more axonal buds to connect distal larger nerves and finally restored to an organized pattern of lamella dominated by corresponding in-muscle nerve branches.